CONCEPT OF BEAUTY AND CHANGE WITH SPECIAL REFERENCE TO PAINTING - Khanna Kakkar, Shruti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
According to Indian concept of art, the only purpose of art is to provide experience of rasa to spectators or conossiurs. This is applicable on all fine arts. The aesthetic concept of ancient fine arts is mentioned in the Chitrasutra of Vishnudharmottar Puran, Samarangan Sutradhar, and Kamasutra but in modern period due to the change in format of fine arts, the concept of beauty has also changed because the concepts of beauty and fine arts are interdependent. In modern Period colour, theme, limbs of art, form etc. have changed. Today form has been distorted, as well as, conceptual art has evolved in visual form which includes installation, performance, new media art, etc. But there is no change in the Process of Rasa Anubhuti and its Nishpatti. After the distortion of form, Rasa and bhava is to be experienced by the spectator.